P39 An analysis of rebleeding rates for variceal haemorrhage at a regional centre: what is the applicability and potential cost for early TIPS?. (6th September 2011) - Harman, D; McCorry, R; Khan, F; O'Neill, R; James, M; Ryder, S; Aithal, G; Guha, I N
Abstract : Introduction: A recent randomised controlled trial demonstrated that the early use of TIPS in patients with Child-Pugh class B and C cirrhosis presenting with acute variceal haemorrhage was associated with a significant reduction in rebleeding and mortality. 1 However, it remains unclear whether an additional economic benefit exists with their approach compared to the current standard of care utilising pharmacological and endoscopic therapies, and rescue TIPS. Aim: We aimed to ascertain how many patients would benefit from early TIPS and the economic implications of introducing this into practice, by observing retrospective data from our tertiary care liver unit. Method: Consecutive patients admitted in 2009 with oesophageal variceal haemorrhage to a tertiary care liver unit at Nottingham University Hospitals (NUH) NHS Trust were identified retrospectively using a dedicated endoscopy database and cross-checking with the emergency medicine database. Patients with non-cirrhotic portal hypertension or isolated gastric varices were not included in our study. Standard management protocols including endoscopic therapy within 24 h, glypressin and prophylactic antibiotics were used. Data were collected on demography, aetiology, rebleeding related hospital admissions and mortality at 12 months. Costs of rebleeding were analysed for all patients meeting inclusion criteria for the original study 1 and included subsequent inpatient care costs and endoscopic/radiological intervention (figures were supplied by the NUH finance and procurement department and based on established national tariffs). The actual cost of rebleeding in our Child Pugh score 7–13 patients was compared to the theoretical cost of introducing early TIPS in this group. Results: 51 cirrhotic patients were admitted to our unit with oesophageal variceal bleeding. 20% of this cohort had Childs A, 40% Childs B and 40% Childs C cirrhosis. The rebleeding rate was 15% at 28 days and 34% at 1-year follow-up. The survival rates were 82% at 28 days and 40% at 1 year. 35 patients (70% of the cohort) had a Child Pugh score of 7–13. Within this subgroup there was a 31% rebleeding rate requiring hospital admission over 12 months and 8% required a TIPS procedure within 12 months. The actual cost of rebleeding episodes for the selected subgroup was 138 446, (3955 per patient). The theoretical cost of early TIPS in this group was calculated as 117 670, (3362 per patient). Assuming a rebleeding rate of 3% with early TIPS1, this strategy has a potential cost reduction of 7% per patient outcome year compared with current standard management. Conclusion: The proportion of variceal bleed patients benefitting from early TIPS could approach 70% in regional centres. This has implications for the provision and organisation of interventional radiology services. Our retrospective analysis suggests marginal cost benefit, complementing the previously observed reduction in rebleeding and mortality; however prospective studies are needed to confirm this.